Carbon nanotube in-situ modified glass fiber as well as preparation method and application thereof
By setting a catalytic layer on the surface of the glass fiber and growing carbon nanotubes in situ, the problem of difficult control of carbon nanotube content and uniformity in the prior art is solved, and efficient and uniform carbon nanotube growth and mechanical properties of glass fibers are achieved. promote.
Patent Information
- Application Number
- CN202411740000.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to efficiently and evenly grow high-content carbon nanotubes on the surface of glass fibers, and the preparation method is complex, making it difficult to support mass production and large-scale applications.
By providing a catalytic layer on the surface of the glass fiber, precursor solution impregnation, drying and reducing using metal complexes and metal nitrate solutions, a catalyst layer is formed, and carbon nanotubes are grown in situ on its surface.
The carbon nanotube content on the surface of the glass fiber is high, uniformity and controllable, and has strong binding force. It is suitable for mass production and improves the mechanical properties of the glass fiber.
Smart Images

Figure CN119430691A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of modified glass fibers, and in particular to a carbon nanotube in-situ modified glass fiber and a preparation method and application thereof. Background Art
[0002] Glass fiber is a widely used inorganic non-metallic material with high insulation, high heat resistance and good mechanical strength. It is often used to manufacture various composite materials, but it is currently facing problems such as single function and poor interface compatibility of composite materials. Carbon nanotubes are a new type of carbon material with unique physical, chemical and mechanical properties. They are considered to be a good functional modifier for traditional fiber materials. At present, carbon nanotubes are mainly compounded with glass fibers to improve the performance of glass fibers.
[0003] The direct chemical vapor deposition method is to pass a glass fiber coated with a catalyst that assists the growth of carbon nanotubes through a carbon-containing atmosphere through a floating chemical vapor deposition method or a fixed chemical vapor deposition method, thereby achieving in-situ generation of carbon nanotubes on the surface of the glass fiber. Studies have shown that carbon nanotubes grown by the floating catalyst method are relatively controllable and can also achieve a high content, but there are only intermolecular van der Waals forces between the carbon nanotubes and the fibers, which also causes the carbon nanotubes to easily detach from the fiber surface and is not suitable for mass production. The fixed catalyst method is considered to be the mainstream method for preparing carbon nanotube-modified glass fibers, but the chemical composition of the catalyst and the glass fiber is very different, and it is still challenging to achieve a uniform and effective catalyst layer preparation.
[0004] At present, it is still very difficult to grow high-content, strongly adsorbed carbon nanotubes on the surface of glass fibers in the existing technology, and the preparation method is complicated, which makes it difficult to support the mass production and large-scale application of carbon nanotube-modified glass fibers. Summary of the invention
[0005] The main purpose of the present invention is to provide a glass fiber modified in situ by carbon nanotubes and its preparation method and application. The preparation method of the glass fiber modified in situ by carbon nanotubes comprises the following steps: S1, setting a catalytic layer on the surface of the glass fiber to obtain a glass fiber with a catalytic layer on the surface; the setting of the catalytic layer includes precursor solution impregnation, drying and reduction; the precursor solution is a mixed solution of a metal complex solution and a metal nitrate solution; the concentration of the metal complex solution is 0.05-0.5 mol / L; S2, in situ growth of carbon nanotubes on the glass fiber with the catalytic layer on the surface to obtain a glass fiber modified in situ by carbon nanotubes. The technical problem to be solved is how to provide a method for modifying glass fiber and in situ growing carbon nanotubes on its surface, so that the carbon nanotube content on the surface of the glass fiber prepared by the method is high, the uniformity is high and the content is controllable between 0.1-60wt%, and the bonding strength between the carbon nanotubes and the glass fiber is strong, and the preparation method is simple and suitable for batch production under continuous process.
[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the method for preparing a glass fiber with in-situ modification of carbon nanotubes proposed by the present invention, it includes the following steps: S1, setting a catalytic layer on the surface of the glass fiber to obtain a glass fiber with a catalytic layer on the surface; the setting of the catalytic layer includes impregnation with a precursor solution, drying and reduction; the precursor solution is a mixed solution of a metal complex solution and a metal nitrate solution; the concentration of the metal complex solution is 0.05-0.5 mol / L; S2, in-situ growth of carbon nanotubes on the glass fiber with a catalytic layer on the surface to obtain a glass fiber with in-situ modification of carbon nanotubes.
[0007] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0008] Preferably, in the aforementioned preparation method, the metal complex solution is selected from at least one of a nickel ammine complex solution and a copper ammine complex solution.
[0009] Preferably, in the aforementioned preparation method, the metal nitrate solution is selected from at least one of cobalt nitrate, iron nitrate, zirconium nitrate, manganese nitrate and zinc nitrate.
[0010] Preferably, in the aforementioned preparation method, the concentration of the metal nitrate solution is 0.01 to 0.1 mol / L.
[0011] Preferably, in the aforementioned preparation method, the drying temperature is 80-220°C.
[0012] Preferably, in the aforementioned preparation method, the drying time is 1 to 3 minutes.
[0013] Preferably, in the aforementioned preparation method, the reduction is carried out in a mixed gas of hydrogen and argon with a volume fraction of 5 to 10%.
[0014] Preferably, in the aforementioned preparation method, the reduction temperature is 200-400°C.
[0015] Preferably, in the aforementioned preparation method, the reduction time is 2 to 5 minutes.
[0016] Preferably, in the aforementioned preparation method, the atmosphere for the in-situ growth of the carbon nanotubes is a mixture of ethylene and argon, or a mixture of acetylene and argon, or a mixture of acetylene, hydrogen and argon.
[0017] Preferably, in the aforementioned preparation method, the volume fraction of the ethylene or acetylene is 2.5-10%.
[0018] Preferably, in the aforementioned preparation method, the growth temperature of the in-situ growth of the carbon nanotubes is 450-800°C.
[0019] Preferably, in the aforementioned preparation method, the growth time of the in-situ growth of the carbon nanotubes is 0.5 to 15 minutes.
[0020] Preferably, in the aforementioned preparation method, the catalytic layer is disposed on the surface of the glass fiber in an intermittent manner or a continuous manner.
[0021] Preferably, in the aforementioned preparation method, the in-situ growth of the carbon nanotubes is carried out in an intermittent manner or a continuous manner.
[0022] Preferably, in the aforementioned preparation method, during the in-situ growth of carbon nanotubes on the glass fiber with a catalytic layer on the surface, the pulling speed of the glass fiber with a catalytic layer on the surface is 0.1 to 3 m / min.
[0023] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: A carbon nanotube in-situ modified glass fiber is prepared according to the preparation method described above; the carbon nanotube content on its surface is 0.1-60wt%.
[0024] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: According to the present invention, an electromagnetic protection composite material is provided, which comprises the glass fiber in-situ modified with carbon nanotubes as described above.
[0025] By means of the above technical solution, the carbon nanotube in-situ modified glass fiber and its preparation method and application proposed by the present invention have at least the following advantages:
[0026] The present invention proposes a method for preparing glass fiber modified by carbon nanotubes in situ, which comprises arranging a catalyst of nickel, copper or nickel-copper alloy on the surface of the glass fiber, adding one or more catalytic promoters of cobalt, iron, zirconium, manganese and zinc to form a catalyst layer, and directly growing carbon nanotubes in situ on the surface of the glass fiber to modify the glass fiber. The method can adjust the pulling speed of the glass fiber with a catalytic layer on the surface to 0.1-3 m / min and the growth conditions of the carbon nanotubes (temperature of 450-800°C and time of 0.5-15 min), so as to not only obtain carbon nanotubes with different lengths and different density distribution results, but also make the carbon nanotubes have the characteristics of highly customized growth; and the method has good versatility on a variety of glass fiber substrates, and the in-situ growth of carbon nanotubes on the surface of the glass fiber will not damage the glass fiber substrate, so that the carbon nanotubes and the glass fiber have a strong bonding force and high adhesion, thereby effectively enhancing the mechanical properties of the glass fiber, and can make the carbon nanotube content high, uniform and controllable, and can prepare a series of carbon nanotube-modified glass fibers with a carbon nanotube content between 0.1 and 60wt%. At the same time, the preparation method is simple, can ensure the setting of the catalytic layer on the surface of the glass fiber and the growth of the carbon nanotubes under a continuous process, and is suitable for mass production.
[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the SEM of the high-silica fiber loaded with 10 wt % of carbon nanotubes according to Example 1 of the present invention.
[0029] Figure 2 This is the SEM of the high-silica fiber loaded with 20 wt % of carbon nanotubes according to Example 2 of the present invention.
[0030] Figure 3 This is the SEM of the alkali-free glass fiber loaded with 40 wt % of carbon nanotubes according to Example 3 of the present invention.
[0031] Figure 4 This is a SEM of the quartz fiber loaded with 40 wt % carbon nanotubes according to Example 4 of the present invention.
[0032] Figure 5 This is the SEM of the S-glass fiber loaded with 60 wt % carbon nanotubes according to Example 5 of the present invention.
[0033] Figure 6 This is the SEM of the S-glass fiber loaded with 0.1 wt % carbon nanotubes according to Example 6 of the present invention.
[0034] Figure 7 1 is a SEM of the quartz fiber loaded with 28 wt % carbon nanotubes according to Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a carbon nanotube in-situ modified glass fiber and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments.
[0036] The first aspect of the present invention provides a method for preparing a glass fiber modified in situ by carbon nanotubes, a method for preparing a glass fiber modified in situ by carbon nanotubes, which comprises the following steps: S1, setting a catalytic layer on the surface of the glass fiber to obtain a glass fiber with a catalytic layer on the surface; the setting of the catalytic layer comprises impregnation with a precursor solution, drying and reduction; the precursor solution is a mixed solution of a metal complex solution and a metal nitrate solution; the concentration of the metal complex solution is 0.05-0.5 mol / L; S2, in-situ growth of carbon nanotubes on the glass fiber with a catalytic layer on the surface to obtain a glass fiber modified in situ by carbon nanotubes.
[0037] The inventors found that the preparation method of the present invention obtains a glass fiber with a catalytic layer on the surface by using a metal complex solution (nickel ammonia complex solution, or copper ammonia complex solution, or a complex solution of nickel ammonia and copper ammonia) and a metal nitrate solution (at least one of cobalt nitrate, iron nitrate, zirconium nitrate, manganese nitrate and zinc nitrate) with a concentration of 0.05-0.5 mol / L on the surface of the glass fiber for precursor solution impregnation, drying and reduction. In the catalytic layer, nickel, copper or nickel-copper alloy is used as a catalyst, and one or more of cobalt, iron, zirconium, manganese and zinc are used as catalyst promoters. Nickel and copper are the main elements that catalyze the growth of carbon nanotubes, which can achieve high-content carbon nanotube generation, and one or more of cobalt, iron, zirconium, manganese and zinc are elements that assist in catalyzing the growth of carbon nanotubes. The reason for using the complex is that it can assist the catalyst to be evenly distributed on the surface of the glass fiber.
[0038] Directly in-situ grow carbon nanotubes on the surface of a glass fiber with a catalytic layer on the surface to modify the glass fiber. The method has good versatility on a variety of glass fiber substrates and will not damage the glass fiber substrate, so that the carbon nanotubes and the glass fiber have a strong bonding force and high adhesion, thereby effectively enhancing the mechanical properties of the glass fiber. Since the surface of the glass fiber is relatively smooth and the carbon nanotubes have a large specific surface area, when the glass fiber is modified in situ, the carbon nanotubes can form a microscopic "anchoring" structure on the surface of the glass fiber, and the nanoscale structure of the carbon nanotubes can fill the microscopic defects on the surface of the glass fiber, thereby increasing the roughness of the interface, increasing the mechanical bite effect, and then improving the bonding force between the two. At the same time, the method can make the carbon nanotube content high, high uniformity and controllable, and can prepare a series of carbon nanotube-modified glass fibers with a carbon nanotube content of 0.1 to 60wt%. The preparation method is simple and suitable for mass production.
[0039] In the present invention, the concentration of the metal nitrate solution is 0.01-0.1 mol / L, that is, the concentration of one or more of cobalt, iron, zirconium, manganese and zinc in the metal nitrate solution is 0.01-0.1 mol / L. In the precursor solution, one or more of cobalt, iron, zirconium, manganese and zinc with a concentration of 0.01-0.1 mol / L is an element that assists in catalyzing the growth of carbon nanotubes. For example, zirconium and manganese have weak catalytic abilities and cannot achieve high-content carbon nanotube generation, so they are used as elements that assist in catalyzing the growth of carbon nanotubes.
[0040] In the present invention, the solvent of the metal complex solution is one of water, ethyl acetate, methanol, ethanol and acetone, preferably ethyl acetate. Thus, the stability of the metal complex solution can be ensured, and the nickel ammonia complex, or the copper ammonia complex, or the complex of nickel ammonia and copper ammonia can be ensured to have good solubility.
[0041] According to the present invention, the drying temperature is 80-220°C. If the temperature is lower than 80°C, the drying will not be thorough and metal particles may agglomerate in the subsequent process. If the temperature is higher than 220°C, the metal catalyst loaded on the surface of the glass fiber will be oxidized.
[0042] According to the present invention, the drying time is 1 to 3 minutes. If the time is less than 1 minute, the drying is incomplete and solvent residues are present. If the time is more than 3 minutes, the metal catalyst loaded on the surface of the glass fiber will be oxidized.
[0043] In the present invention, there is no particular limitation on the drying method, and those skilled in the art can select it according to actual needs, for example, it can be oven drying, infrared heating drying, etc. Considering that infrared is a relatively easy to implement static heating method, and the requirements for the device in the continuous equipment are relatively low, therefore, the drying in the present invention is preferably infrared heating drying.
[0044] According to the present invention, the reduction is carried out in a mixture of hydrogen and argon with a volume fraction of 5 to 10%. Argon acts as a protective gas, and the volume fraction of the mixture of hydrogen and argon is 5 to 10%, mainly from the perspective of balancing the reduction efficiency and safety. A low hydrogen content leads to a poor reduction efficiency, and a high hydrogen content leads to a high safety risk.
[0045] According to the present invention, the reduction temperature is 200-400°C, and the reduction time is 2-5 minutes. If the reduction temperature is less than 200°C, or the reduction time is less than 2 minutes, the catalyst loaded on the surface of the glass fiber will not be completely reduced, affecting the catalytic effect; if the temperature is greater than 400°C, or the reduction time is greater than 5 minutes, the energy consumption will increase, and the problem of metal catalyst particle agglomeration may also be caused.
[0046] In the present invention, the catalytic layer is provided on the surface of the glass fiber by treating the glass fiber with a precursor solution, then drying the solvent, and heat treating the glass fiber in a reducing atmosphere. This process can be intermittent or continuous through a specific conveying mechanism, but in order to ensure the consistency and efficiency of the catalytic layer, the continuous setting method is preferred.
[0047] According to the present invention, the in-situ growth method of the carbon nanotubes is chemical vapor deposition. The in-situ growth of carbon nanotubes is based on chemical vapor deposition (including plasma enhanced chemical vapor deposition). This process can be either intermittent or continuous growth of carbon nanotubes through a specific conveying mechanism. In order to ensure the consistency and controllability of the growth of carbon nanotubes, the continuous growth method of carbon nanotubes is preferred.
[0048] According to the present invention, carbon nanotubes are grown in situ on the surface of glass fibers. First, a catalyst (such as a metal catalyst) is loaded on the surface of the glass fibers. Then, the glass fibers are placed in an environment of a carbon source gas (ethylene or acetylene). Under high temperature conditions, the carbon source gas is decomposed under the action of the catalyst and carbon nanotubes are grown on the surface of the glass fibers. The in situ growth method can form a closer bond between the carbon nanotubes and the glass fibers because the carbon nanotubes are grown directly on the surface of the glass fibers, and there may be chemical bonding or strong physical adsorption between the two.
[0049] According to the present invention, the atmosphere for the in-situ growth of the carbon nanotubes is a mixture of ethylene and argon, or a mixture of acetylene and argon, or a mixture of acetylene, hydrogen and argon. The carrier gas for the growth of the carbon nanotubes is argon and / or argon, and the carbon source gas for the growth of the carbon nanotubes is ethylene or acetylene, and the volume fraction of the ethylene or acetylene is 2.5-10%. If the volume fraction of the carbon source gas (ethylene or acetylene) is lower than 2.5%, the expected content of carbon nanotubes cannot be obtained; if the volume fraction of the carbon source gas (ethylene or acetylene) is higher than 10%, the growth rate of the carbon nanotubes is fast and other carbon impurities (such as carbon black) are also generated.
[0050] According to the present invention, the growth temperature of the in-situ growth of the carbon nanotubes is 450-800°C. If the temperature is lower than 450°C, impurities such as amorphous carbon will be generated, resulting in the failure to generate carbon nanotubes; if the temperature is higher than 800°C, the strength of the glass fiber will be damaged, resulting in the possibility of breaking the glass fiber.
[0051] According to the present invention, the growth time of the in-situ growth of the carbon nanotubes is 0.5 to 15 minutes. If the time is less than 0.5 minutes, the expected carbon nanotube content cannot be obtained; if the time is greater than 15 minutes, it is difficult to achieve the desired carbon nanotube content while ensuring a continuous process.
[0052] According to the present invention, during the in-situ growth of carbon nanotubes on the glass fiber with a catalytic layer on the surface, the pulling speed of the glass fiber with a catalytic layer on the surface is 0.1 to 3 m / min, for example, it can be 0.1 m / min, 0.5 m / min, 1.0 m / min, 1.5 m / min, 2.0 m / min, 2.5 m / min and 3 m / min. It should be noted that in the present invention, the pulling speed of the glass fiber with a catalytic layer on the surface refers to: during the in-situ growth of carbon nanotubes on the glass fiber with a catalytic layer on the surface, the rate at which it is pulled out from the bobbin. Therefore, by adjusting the pulling speed of the glass fiber to 0.1 to 3 m / min, the in-situ growth time of the carbon nanotubes can be further controlled to be 0.5 to 15 minutes, thereby controlling the content of carbon nanotubes.
[0053] A particularly preferred method for in-situ growth of carbon nanotubes of the present invention is to pull a glass fiber provided with a surface catalytic layer from a spool at a rate of 0.1 to 3 m / min, pass it through a carbon nanotube growth chamber at a temperature of 450 to 800°C, grow it in a carbon-containing gas atmosphere for 0.5 to 15 minutes to obtain carbon nanotubes with a content of 0.1 to 60 wt%, and then wind it with a synchronous spool to obtain a glass fiber modified in situ with carbon nanotubes.
[0054] In the present invention, the size and shape of the carbon nanotube growth chamber can be determined according to the amount of glass fiber processed in a single batch, and the present invention does not impose any limitation on this. However, a tubular square chamber with a length of 1.5 m, a width of 0.1 m, and a height of 0.05 m is preferred, which is conducive to higher growth efficiency while being easy to maintain.
[0055] The second aspect of the present invention provides a carbon nanotube in-situ modified glass fiber, which is prepared according to the preparation method as described above; the content of carbon nanotubes on its surface is 0.1-60wt%. Therefore, the content of carbon nanotubes is high, the uniformity is high, and the content is controllable between 0.1-60wt%, and the bonding strength between carbon nanotubes and glass fiber is strong.
[0056] A third aspect of the present invention provides an electromagnetic shielding composite material, which includes the glass fiber in-situ modified with carbon nanotubes as described above.
[0057] It should be noted that the glass fiber can be any type of commercially available glass fiber, for example, alkali-free glass fiber, S-glass fiber, quartz fiber, high-silica fiber, etc. Therefore, the carbon nanotube in-situ modification of the present invention can be applied to a variety of glass fiber substrates and has good versatility.
[0058] It should be noted that although carbon nanotubes can be grown on the surface of glass fibers by the method of the technical solution of the present invention, the softening temperatures of various glass fibers in the actual process should also be taken into consideration. For example, under a certain process formula, the in-situ growth of carbon nanotubes needs to be grown in an environment with a temperature above 600°C. In this case, alkali-free glass fibers should not be used as the substrate, because the softening point of alkali-free glass fibers is between 550 and 600°C. The growth temperature of carbon nanotubes higher than the softening point of alkali-free glass fibers will cause the alkali-free glass fibers to become brittle, resulting in a significant decrease in the strength of the modified alkali-free glass fibers.
[0059] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0060] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0061] Example 1
[0062] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 10 wt % on the surface of high-silica fiber.
[0063] The high-silica fiber is pulled out from the bobbin at a rate of 3m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.05mol / L nickel-ammine complex in ethyl acetate and contains 0.025mol / L cobalt nitrate. After impregnation for 2.0min, it is dried by pulling at the same rate of 3m / min, and heated to 150°C under an infrared lamp for 2.0min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 250°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 5%, and the reduction time is 2.5min. After the reduction is completed, a high-silica fiber with a surface catalytic layer is obtained.
[0064] The high-silica fiber with a surface catalytic layer is pulled out from the spool at a rate of 2m / min and allowed to stay in a carbon nanotube growth chamber at a temperature of 800°C for 0.75min. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5m, a width of 0.1m, and a height of 0.05m. The gas atmosphere of the growth chamber is a mixture of ethylene and argon, in which the volume fraction of ethylene is 5%. After the high-silica fiber with a surface catalytic layer passes through the carbon nanotube growth chamber, a high-silica fiber loaded with 10wt% carbon nanotubes can be obtained, such as Figure 1 shown.
[0065] Example 2
[0066] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 20 wt % on the surface of high-silica fiber.
[0067] The high-silica fiber is pulled out from the bobbin at a rate of 3m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.05mol / L nickel-ammine complex in ethyl acetate and contains 0.04mol / L cobalt nitrate. After impregnation for 1.0min, it is dried by pulling at the same rate of 3m / min, and heated to 180°C under an infrared lamp for 1.5min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 250°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 5%, and the reduction time is 3.0min. After the reduction is completed, a high-silica fiber with a surface catalytic layer is obtained.
[0068] The high-silica fiber with a surface catalytic layer was pulled out from the spool at a rate of 1.5 m / min and allowed to stay in a carbon nanotube growth chamber at a temperature of 800°C for 1.0 min. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5 m, a width of 0.1 m, and a height of 0.05 m. The gas atmosphere of the growth chamber is a mixture of acetylene and argon, in which the volume fraction of acetylene is 5%. After the high-silica fiber with a surface catalytic layer passes through the carbon nanotube growth chamber, a high-silica fiber loaded with 20 wt% of carbon nanotubes can be obtained, such as Figure 2 shown.
[0069] Example 3
[0070] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 40 wt % on the surface of alkali-free glass fiber.
[0071] The alkali-free glass fiber is pulled out from the bobbin at a rate of 1m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.2mol / L of nickel-ammonia and copper-ammonia complex (the mass ratio of nickel and copper is 1:1) in ethyl acetate and contains 0.05mol / L of ferric nitrate. After impregnation for 2.5min, it is dried by pulling at the same rate of 1m / min, and heated to 220℃ under an infrared lamp for 1.0min until the organic solvent is completely volatilized. Then, thermal reduction is carried out, the reduction temperature is set at 400℃, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 10%, and the reduction time is 5min. After the reduction is completed, an alkali-free glass fiber with a surface catalytic layer is obtained.
[0072] The alkali-free glass fiber with a surface catalytic layer was pulled out from the spool at a rate of 0.5 m / min and allowed to stay in a carbon nanotube growth chamber at 550°C for 3 minutes. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5 m, a width of 0.1 m, and a height of 0.05 m. The gas atmosphere of the growth chamber is a mixture of acetylene and argon, in which the volume fraction of acetylene is 7.4%. After the alkali-free glass fiber with a surface catalytic layer passes through the carbon nanotube growth chamber, an alkali-free glass fiber loaded with 40 wt% carbon nanotubes can be obtained, such as Figure 3 shown.
[0073] Example 4
[0074] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 40 wt % on the surface of quartz fiber.
[0075] The quartz fiber is pulled out from the bobbin at a rate of 1m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.5mol / L ethyl acetate solution of nickel-ammine complex and contains 0.05mol / L manganese nitrate. After impregnation for 0.75min, it is dried by pulling at the same rate of 1m / min, and heated to 150°C under an infrared lamp for 2.0min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 350°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 10%, and the reduction time is 5min. After the reduction is completed, a quartz fiber with a surface catalytic layer is obtained.
[0076] The quartz fiber with a surface catalytic layer is pulled out from the spool at a rate of 0.2m / min and allowed to stay in a carbon nanotube growth chamber at 750°C for 7.5min. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5m, a width of 0.1m, and a height of 0.05m. The gas atmosphere of the growth chamber is a mixture of acetylene and argon, in which the volume fraction of acetylene is 4.4%. After the quartz fiber with a surface catalytic layer passes through the carbon nanotube growth chamber, a quartz fiber loaded with 40wt% carbon nanotubes can be obtained, such as Figure 4 shown.
[0077] Example 5
[0078] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 60 wt % on the surface of S-glass fibers.
[0079] The S-glass fiber is pulled out from the bobbin at a rate of 1m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.5mol / L ethyl acetate solution of nickel-ammine complex, and contains 0.05mol / L manganese nitrate and 0.025mol / L zinc nitrate. After impregnation for 0.5min, it is pulled and dried at the same rate of 1m / min, and heated to 150°C under an infrared lamp for 2.0min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 400°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 10%, and the reduction time is 5min. After the reduction is completed, an S-glass fiber with a surface catalytic layer is obtained.
[0080] The S-glass fiber provided with a surface catalytic layer is pulled out from the bobbin at a rate of 0.1 m / min and allowed to stay in a carbon nanotube growth chamber at 750°C for 15 minutes. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5 m, a width of 0.1 m, and a height of 0.05 m. The gas atmosphere of the growth chamber is a mixture of acetylene and argon, in which the volume fraction of acetylene is 10%. After the S-glass fiber provided with a surface catalytic layer passes through the carbon nanotube growth chamber, an S-glass fiber loaded with 60 wt% carbon nanotubes can be obtained, such as Figure 5 shown.
[0081] Example 6
[0082] This example is used to illustrate the method of in-situ growing carbon nanotubes with a content of 0.1 wt % on the surface of S-glass fibers.
[0083] The S-glass fiber is pulled out from the bobbin at a rate of 3m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.05mol / L of ethyl acetate solution of copper ammonia complex and contains 0.01mol / L of zinc nitrate. After impregnation for 2.5min, it is dried by pulling at the same rate and heated to 80°C under an infrared lamp for 3.0min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 200°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 5%, and the reduction time is 2min. After the reduction is completed, an S-glass fiber with a surface catalytic layer is obtained.
[0084] The S-glass fiber provided with a surface catalytic layer is pulled out from the bobbin at a rate of 3m / min and allowed to stay in a carbon nanotube growth chamber at 750°C for 0.5min. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5m, a width of 0.1m, and a height of 0.05m. The gas atmosphere in the growth chamber is a mixture of ethylene and argon, in which the volume fraction of ethylene is 2.5%. After the S-glass fiber provided with a surface catalytic layer passes through the carbon nanotube growth chamber, an S-glass fiber loaded with 0.1wt% carbon nanotubes can be obtained, such as Figure 6 shown.
[0085] Comparative Example 1
[0086] This comparative example is used to illustrate a method for in-situ growing carbon nanotubes with a content of 28 wt % on the surface of quartz fiber without using nickel-ammonia (or copper-ammonia) complex as a precursor solution.
[0087] The quartz fiber is pulled out from the bobbin at a rate of 1m / min and impregnated with a precursor solution at this rate. The precursor solution is composed of 0.5mol / L nickel nitrate in ethyl acetate and contains 0.05mol / L manganese nitrate. After impregnation for 0.75min, it is dried by pulling at the same rate of 1m / min, and heated to 150°C under an infrared lamp for 2.0min until the organic solvent is completely volatilized. Subsequently, thermal reduction is carried out, the reduction temperature is set at 350°C, the reducing atmosphere is a mixture of hydrogen and argon with a volume fraction of 10%, and the reduction time is 5min. After the reduction is completed, a quartz fiber with a surface catalytic layer is obtained.
[0088] The quartz fiber with a surface catalytic layer is pulled out from the spool at a rate of 0.2m / min and allowed to stay in a carbon nanotube growth chamber at 750°C for 7.5min. The carbon nanotube growth chamber is a square tube cavity with a length of 1.5m, a width of 0.1m, and a height of 0.05m. The gas atmosphere of the growth chamber is a mixture of acetylene and argon, in which the volume fraction of acetylene is 4.4%. After the quartz fiber with a surface catalytic layer passes through the carbon nanotube growth chamber, a quartz fiber loaded with 40wt% carbon nanotubes can be obtained, such as Figure 7 shown.
[0089] It can be seen from Examples 1-7 that the preparation method proposed in the present invention uses nickel ammonia complex, copper ammonia complex, or a complex of nickel ammonia and copper ammonia as a precursor solution, and the carbon nanotubes on the surface of the prepared glass fiber have a high content and high uniformity, and the content is controllable between 0.1-60wt%, and the bonding strength between the carbon nanotubes and the glass fiber is strong.
[0090] It can be seen from Example 4 and Comparative Example 1 that, under the same process and the same glass fiber substrate, but without using nickel ammonia complex, copper ammonia complex, or nickel ammonia and copper ammonia complex as the precursor solution, the content of carbon nanotubes generated on the surface of the quartz fiber decreases from 40wt% to 28wt%, indicating that after not using the complex, the content of carbon nanotubes is significantly reduced; and according to Figure 7 As shown in the SEM image, the distribution of carbon nanotubes on the surface of quartz fiber in Comparative Example 1 is extremely uneven, the bonding strength between carbon nanotubes and quartz fiber is weak, and there are obvious peeling and agglomeration phenomena.
[0091] The technical features in the claims and / or the specification of the present invention can be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the claims and / or technical features is also within the protection scope of the present invention.
[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a glass fiber in-situ modified with carbon nanotubes, characterized in that: It includes the following steps: S1. Arranging a catalytic layer on the surface of the glass fiber to obtain a glass fiber having a catalytic layer arranged on the surface; the catalytic layer arrangement includes impregnation with a precursor solution, drying and reduction; The precursor solution is a mixed solution of a metal complex solution and a metal nitrate solution; The concentration of the metal complex solution is 0.05-0.5 mol / L; S2. In-situ growth of carbon nanotubes is performed on the glass fiber with a catalytic layer on the surface thereof to obtain a glass fiber in-situ modified with carbon nanotubes.
2. The preparation method according to claim 1, characterized in that: The metal complex solution is selected from at least one of a nickel ammine complex solution and a copper ammine complex solution; The metal nitrate solution is selected from at least one of cobalt nitrate, iron nitrate, zirconium nitrate, manganese nitrate and zinc nitrate; The concentration of the metal nitrate solution is 0.01-0.1 mol / L.
3. The preparation method according to claim 1, characterized in that: The drying temperature is 80-220° C. and the drying time is 1-3 minutes.
4. The preparation method according to claim 1, characterized in that: The reduction is carried out in a mixed gas of hydrogen and argon with a volume fraction of 5 to 10%; The reduction temperature is 200-400°C; the reduction time is 2-5 minutes.
5. The preparation method according to claim 1, characterized in that: The atmosphere for the in-situ growth of the carbon nanotubes is a mixture of ethylene and argon, or a mixture of acetylene and argon, or a mixture of acetylene, hydrogen and argon; The volume fraction of the ethylene or acetylene is 2.5-10%.
6. The preparation method according to claim 1, characterized in that: The growth temperature of the in-situ growth of the carbon nanotubes is 450-800° C. and the growth time is 0.5-15 minutes.
7. The preparation method according to claim 1, characterized in that: The method of providing the catalytic layer on the surface of the glass fiber is an intermittent method or a continuous method; The in-situ growth mode of the carbon nanotubes is an intermittent mode or a continuous mode.
8. The preparation method according to claim 1, characterized in that: During the in-situ growth of carbon nanotubes on the glass fiber with the catalytic layer on the surface, the pulling speed of the glass fiber with the catalytic layer on the surface is 0.1-3 m / min.
9. A glass fiber modified by in-situ carbon nanotubes, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8; the content of carbon nanotubes on its surface is 0.1 to 60 wt%.
10. An electromagnetic protection composite material, characterized in that: It comprises the carbon nanotube in-situ modified glass fiber as claimed in claim 9.
Citation Information
Patent Citations
Method for growing carbon nanotube by loading core-shell structure catalyst on surface of carbon fiber and application
CN116815499A
Carbon nanotube modified fiber material as well as preparation method and application thereof
CN118441465A
Enhanced conductivity nanocomposites and method of use thereof
US20030151030A1
Process for Preparing a Monolithic Catalysis Element Comprising a Fibrous Support and Said Monolithic Catalysis Element
US20140287912A1
Cited By
Composite sound absorption material based on carbon nanotube modified glass fibers and preparation method and application thereof
CN121405376A
Carbon nanotube modified glass fiber composite sound-absorbing material, preparation method and application thereof
CN121405376B